CHALLENGES OF INTERPRETATION IN MEDIA - Ergasheva , Arofat Tolib qizi (Educational Research in Universal Sciences, 2023)
The subject of research in this article is the challenges of interpretation in media. The purpose of the work is to theoretically interpret the mass media discourse in the context of modern society and practice of media communications. The study of mass media discourse considers the features of the platforms, its production and importance, as well as its representation. The work uses a set of methods: descriptive, comparative and interpretative methods.